Spectroscopy Studies on the Status of Aloin in Aloe vera and Commercial Samples - R. Ashok Kumar1 and M. Gayathiri3, S. Ravi1*, P. Kabilar2, S. Velmurugan1 (Journal of Experimental Sciences, 2011)
This study was carried out at Department of Physics and Department of Horticulture, Annamalai University, Annamalai Nagar, Tamil Nadu, India to identity and characterize the phenolic antroquitones (Aloin-A and B) from Aloe Vera samples. Among the lewenth different samples forms of Aloe vera. The Aloe vera sap contain more aloin of 4 hydroxy aloin. Aloe vera leaf, gel,root commercial gel and commercial soap samples were characterized by FT-IR and UV Spectroscopy techniques. The result were discussed the above studies.